A changing economic vote in Western Europe? Long-term vs. short-term forces. Issue 1 (21st November 2018) - Dassonneville, Ruth; Lewis-Beck, Michael S.
Abstract: Considerable research shows the presence of an economic vote, with governments rewarded or punished by voters, depending on the state of the economy. But how stable is this economic vote? A current argument holds its effect has increased over time, because of weakening long-term social and political forces. Under these conditions, short-term forces, foremostly the economic issue, can come to the fore. A counter-argument, however, sees the economic vote effect in decline, due to globalization. Against these rival hypotheses rests the status-quo argument: the economic vote effect remains unchanged. To test these claims, we estimate carefully specified models of the incumbent vote, at both the individual and aggregate levels. Western European elections provide the data, with particular attention to Denmark, Germany, Great Britain, Italy, The Netherlands, Norway, and Sweden. Perhaps surprisingly, we find the economic vote to be stable over time, a 'standing decision' rule that voters follow in national elections.